"Etude des propriétés optoélectroniques du matériau ternaire emplecitite CuBiS2 pour des applications photovoltaïques" - MIRA, Nesrine; BOUKHADEM, Oumesaad (Univ M'sila, 2020)
In this work, we studied the structural, electronic and optical properties of CuBiS2 using density functional theory (DFT) based on the full-potential linear augmented plane wave (FPLAPW) method. approximation (LDA) by Walter Cohen was used. Additionally which successfully corrects the band-gap problem, was used for the band structure calculations. The calculated lattice constants and band-gap values, for these alloys are in good agreement with the available theoretical and experimental data. The dielectric function and absorption coefficient are calculated to investigate the optical properties. Electronic and optical properties reveal that these alloys should be very useful for applications in photonics, optoelectronics. Résumé Dans ce travail, nous avons étudié les propriétés structurales, électroniques et optiques de CuBiS2 en utilisant la théorie fonctionnelle de densité (DFT) basée sur la méthode d'onde plane augmentée linéaire (FP-LAPW). l'approximation (LDA) de Walter Cohen a été utilisée pour les calculs de structure de bande. Ainsi que la fonction diélectrique est calculées pour étudier les propriétés optiques. Les propriétés électroniques et optiques révèlent que ces alliages sont très utiles pour des applications en photonique, optoélectronique.
Keywords: CuBiS2, FP-LAPW, DFT, propriétés électronique,Chalcopyrite, Wien2k.; CuBiS2, FP-LAPW, DFT, Electronic properties ,Chalcopyrite, Win2k.